PEMBELAJARAN KITAB BULUGH AL-MARAM MIN ADILLAT AL-AHKAM DALAM MENINGKATKAN PEMAHAMAN FIQIH SISWA DI MADRASAH ALIYAH MIFTAHUL HUDA TANJUNGANOM - Dimas Sanjaya; Jasminto (PAI FAI UNHASY Tebuireng Jombang, 2024)
Learning is an activity designed to create a person's state of being able to seek knowledge well. Learning is very important because every human being needs to study religion. Studying Islam cannot be separated from referring to the hadith books of the Prophet Muhammad SAW. In Madrasah Aliyah Miftahul Huda Tanjunganom, for example, yellow books such as Bulughul Maram are taught to students. This observation aims to describe how the study of the book of Bulughul Maram at MA Miftahul Huda Tanjunganom can improve students' understanding of fiqh. This research is included in the category of field research with a qualitative approach and descriptive methods. Data was collected through interviews, observations, and documentation with informants such as Madrasah Heads, teachers, and students. The results of the study resulted in students' understanding of fiqh increasing after participating in the study of this book, as evidenced by tests that showed significant changes. Although learning is going well, challenges arise from the lack of interest in learning students. However, thanks to the hard work of teachers, this challenge was successfully overcome and students' understanding of fiqh increased after participating in the study of the book of Bulughul Maram.